2012
DOI: 10.2139/ssrn.2118748
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Public Debt Dynamics in Italy, 1861-2009

Abstract: We examine the historical dynamics of government debt in Post-Unification Italy, from 1861 to 2009. Unit root tests for the debt-GDP ratio are unable to reject either the non-stationarity or the stationarity null hypothesis. Controlling debt dynamics for fiscal feedback policies of the Barro-Bohn style, however, the debt-GDP ratio is found to be mean-reverting. Mean-reversion in the debt-GDP ratio is due not only to a nominal growth dividend, but also to a positive response of primary surpluses to variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Wyplosz (2006), Staehr (2008) and others apply the same methodology to European datasets and find some evidence of positive feedback from the debt stock to the primary balance but also conclude that the feedback is difficult to estimate precisely because the data series are short. Piergallini & Postigliola (2012) find that the primary balance in Italy has exhibited a positive reaction to the debt stock and conclude that politicians have taken corrective measures to ensure the sustainability of public finances in Italy. Estimating a fiscal reaction function for Brazil using monthly data, de Mello (2008) finds that the primary balance reacts positively and strongly to the lagged debt stock.…”
Section: Related Literaturementioning
confidence: 93%
“…Wyplosz (2006), Staehr (2008) and others apply the same methodology to European datasets and find some evidence of positive feedback from the debt stock to the primary balance but also conclude that the feedback is difficult to estimate precisely because the data series are short. Piergallini & Postigliola (2012) find that the primary balance in Italy has exhibited a positive reaction to the debt stock and conclude that politicians have taken corrective measures to ensure the sustainability of public finances in Italy. Estimating a fiscal reaction function for Brazil using monthly data, de Mello (2008) finds that the primary balance reacts positively and strongly to the lagged debt stock.…”
Section: Related Literaturementioning
confidence: 93%
“…Wyplosz (2006), Staehr (2008) and others implement the same methodology on European datasets and find some evidence of a positive feedback from the debt stock to the primary balance, but the feedback is often imprecisely estimated due to short data series. Piergallini & Postigliola (2012) find that the primary balance in Italy has exhibited a positive reaction to the debt stock and argue that this suggests that politicians have taken corrective measures to ensure the sustainability of public finances in Italy. Estimating a fiscal reaction function for Brazil using monthly data, de Mello (2008) finds that the primary balance reacts positively and strongly to the lagged debt stock.…”
Section: Related Literaturementioning
confidence: 95%
“…Casadio et al (2012) showed that a policy intervention aimed to stimulate the GDP growth over 1.8% allows to reach the target 100% debt-to-GDP ratio. The empirical evidence by Piergallini and Postigliola (2012) shows the occurrence of a significantly positive reaction of primary surpluses to debt when the debt/GDP ratio exceeded the trigger value of 110%. Accounting for structural breaks, Trachanas and Katrakilidis (2013) suggested that the sustainability of the fiscal deficits in Italy holds only in a weak sense.…”
Section: Empirical Literaturementioning
confidence: 99%